CREATION OF A SINGLE EDUCATIONAL SPACE OF POSTGRADUATE EDUCATIONAL ESTABLISHMENTS - Olena Murashchenko (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article theoretically justified the ways of creating a single educational space of postgraduate educational establishments on the basis of integration of educational, professional, research and social and cultural activities of teachers as a necessary component of preparation of primary school teachers for integrated learning and examines different approaches to education. Studies of domestic and foreign scientists in comparative analysis with the concept of «educational environment» and characterized the psychological and pedagogical conditions of the turn of the integration educational space of postgraduate institutions. On the basis of the analysis, the author proposed to identify a system of components that make up the structure of the space of postgraduate education and are integrators in its creation, the emphasis is placed on the conceptual integration bases for the implementation of the characteristics of the components. It is emphasized on the unconventionality of educational and professional activity of elementary school teachers in the aspect of psycho-activity, activation of teachers' research activity as a factor of improving the quality of their training, organization of socio-cultural activity in the conditions of postgraduate education as reasons for the development of adaptability and interpersonal relations. Particular attention was paid to the use of integration of innovative activities that provide a dialectical interaction of the logic of the educational process, the development of subjects of learning and sociocultural adaptation in the new educational environment to achieve the didactic task of preparing teachers for the introduction of integration education in primary school.